THE FATHER OF WHITE REVOLUTION - Gopalakrishnan, K.V. (SCHOOL SCIENCE, 2012)
Our country has the largest cattle population of any nation in the world. Our people have traditionally venerated cows. Does this mean that we have a very efficient dairy industry? Unfortunately, the answer is No. Most of our cattle are deplorably fed and maintained and hence our yield of milk per animal is one of the lowest in the world. Nevertheless, there has been a considerable improvement in the situation over the past 25 years due to a remarkable programme Operation Flood, which has become irrevocably linked in the minds of discerning people with the moving spirit behind it, Dr. Verghese Kurien. It has been one of the outstanding successes that we have achieved since Independence.